Adoption of Technology for Reading Purposes: A Study of E-Books Acceptance - Mateus Martins; Josivania Silva Farias; Pedro Henrique Melo Albuquerque; Danilo Santana Pereira (BBR: Brazilian Business Review)
This study aims to verify the acceptance of e-books by identifying the effects of the variables Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Habit, Price Value, and Hedonic Motivation, moderated by Age, Gender and Experience on the intention of use and actual use of this technology. To verify the effects of the relations between these variables, we applied the Unified Theory of Acceptance and Use of Technology 2 model (VENKATESH; THONG; XU, 2012). Out of a universe of 118,456 Brazilian citizens directly involved with education, 1,013 completed an online survey. We analyzed the data via structural equations modeling; we obtained generalized least squares and standard errors via resampling (Jackknife). The study concludes that Habit, Effort Expectancy and Facilitating Conditions are important for the adoption of e-books, and that Age, Gender and Experience are crucial moderators of these relations.